(untitled) (University Journal of Zoology, Rajshahi University, 2012)
In the present investigation, 30 Long-Evans were examined. Out of 30, 23 rats were infected by helminth parasites, two species of helminth parasites from two taxonomic groups were identified, cestode Hymenolepis nana and nematode Syphacia muris. The prevalence and intensity of parasites were quite different in different groups of helminth parasites in hosts. The prevalence and intensity of infestation of cestodes were 26.67% and 5.57±1.5 while higher of nematodes 66.67% and 60.85±8.1 in the Long-Evans respectively. Hymenolepis nana was found in small intestine and Syphacia muris in all parts of the alimentary tract. The prevalence and intensity of infestation was 36.67% and 5.09±1.6 respectively in small intestine. The prevalence of infestation was similar both in large intestine and caecum (63.33%), and in rectum (63.33%). The intensity of infestation was 24±3.30 and 39.16±4.10 in large intestine and caecum, and in rectum respectively. Key words: Long-Evans; Rattus norvegicus; cestodes; nematodes; prevalence; intensity. DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9464 UJZRU 2010; 29(1): 41-45